2015
DOI: 10.1177/1744629515591410
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Colourful Semantics on narrative skills in children with intellectual disabilities in Sri Lanka

Abstract: The Colourful Semantics approach is an effective therapy approach to support development of narrative skills in children with intellectual difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Various classroom training studies involving narratives have already been successfully carried out with preschool non-TD children (e.g., [91,92]). In this regard, [92] demonstrated that narrative interventions are a promising and effective strategy to teach oral narration to children with risk factors and narrative language delays, who may benefit from it in terms of their short-term and longterm narrative retelling skills (see also [93][94][95][96]). We claim that more effective interventions should include training focused on not only children's speech but also their gestures and general multimodal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Various classroom training studies involving narratives have already been successfully carried out with preschool non-TD children (e.g., [91,92]). In this regard, [92] demonstrated that narrative interventions are a promising and effective strategy to teach oral narration to children with risk factors and narrative language delays, who may benefit from it in terms of their short-term and longterm narrative retelling skills (see also [93][94][95][96]). We claim that more effective interventions should include training focused on not only children's speech but also their gestures and general multimodal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The Past Tense Intervention (PaTI) programme was developed by the first author and specifically targets regular simple past tense marking in English contrasting it with the present continuous tense. The programme uses a combination of the following strategies that have been used in previous successful interventions: modelling of expressive language targets in context (Buckley, 1993; Sepúlveda et al, 2013; Yoder et al., 2014); use of recasts (Camarata et al, 2006); multiple repetitions of the target structure (Burgoyne et al., 2012; Sepúlveda et al, 2013); use of text to support learning, comprehension and memory for spoken language (Buckley, 1993; Buckley, 1995; Mengoni et al., 2014) and explicit explanation of grammatical rules (Bibi et al., 2019; Hettiarachchi, 2015; Tobin & Ebbels, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Several other small scale studies report successful use of structured programmes for teaching syntax (e.g., colour coding and/or shape coding parts of the language) with children with intellectual difficulties that include children with Down syndrome (Bibi et al., 2019; Hettiarachchi, 2015; Tobin & Ebbels, 2018). An intervention using a shape coding system (Tobin & Ebbels, 2018) found significant gains for tense and plural agreement marking in copulas and auxiliaries ( d = 0.92) for 8/11 participants (six of whom had Down syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…O CS vem obtendo resultados muito satisfatórios em diferentes países. Como atesta o trabalho realizado por [Hettiarachchi 2016], indicando mudanças positivas pós-intervenção nas medidas de habilidades narrativas qualitativas e quantitativas empreendidas sobre o conteúdo e estruturas sintáticas formadas pelo CS.…”
Section: Trabalhos Relacionadosunclassified